PENGARUH PERILAKU KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI YANG DIMODERASI MOTIVASI KERJA - Widiyanto, Broto -; -, Sutarno - (Universitas Slamet Riyadi, 2011)
ABSTRACT The experiment was conducted at PT Pos Indonesia (Persero) Solo branch Jalan Sudirman No.. 8. The data used are primary data taken from questionnaires to the respondents. All variables are taken through a questionnaire with as much data as 50 people. Data analysis tool that is used by multiple regression analysis, moderating regression analysis, t test, F test, and the coefficient of determination. Based on the results of hypothesis testing, it can be concluded: (1) There is a significant effect of transformational leadership behavior on employee performance, (2) There is no significant influence of organizational culture on employee performance, (3) There is a significant effect of work motivation on employee performance, (4) Motivation work does not moderate the effect of transformational leadership behavior on employee performance; (5) Motivation does not moderate the influence of organizational culture on employee performance in PT Pos Indonesia (Persero) Solo branch. Â Keywords: Transformational leadership, organizational culture, work motivation, performance.